ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT MISKIN SEBAGAI PENGEMIS DAN PEMULUNG DI KOTA MALANG - Susilo; Fatoni, Adi (Journal of Development Economic and Social Studies, 2023)
This study aims to examine the influence of education, income, gender, marital status, origin, and family dependents on the decision of impoverished individuals to engage in begging or waste picking in Malang City. As the second most populous city in East Java, Malang City faces a significant poverty issue, resulting in social problems such as the proliferation of beggars and waste pickers. These individuals fall under the category of Social Welfare Problematic Individuals (PMKS) and coexist with social welfare programs implemented by the Malang City Social Service. A quantitative research approach was employed, utilizing binary logistic regression analysis. The study sample consisted of 72 respondents. The results of the logistic regression analysis revealed that income, gender, and marital status significantly influence the decisions of individuals, while the remaining variables do not show significant influence. The findings of this study shed light on the factors that affect impoverished individuals' choices to engage in begging or waste picking and provide insights for interventions and policy development to address poverty-related issues in Malang City.